TZNT alloy for surgical implant applications: A systematic review - Nasibi, Shima; Alimohammadi, Kiana; Bazli, Leila; Eskandarinezhad, Sara; Mohammadi, Ali; Sheysi, Niloufar (Journal of Composites and Compounds, 2020)
Nowadays, Ti–Nb–Ta–Zr (TZNT) alloy have attracted attention as new titanium alloy material for surgical implant applications due to its biocompatibility, great corrosion behavior, low cytotoxicity, and enhanced wear resistance, biological and mechanical properties. There is a great need to improve the implant properties which can be achieved through a combined solution of titanium alloy (TNZT) with low elastic modulus in the physiological environment of the body. Moreover, it protects the surgical implant from inflammation, infection, adverse soft tissue reaction to particulate debris and implant fracture. Therefore this review aimed to improve the quality of the surgical implant applications to enhance the working life and prevent failure by adding four matrices containing niobium, zirconium, tantalum, and silicon. Hence, TZNT alloy can be developed to be a promising candidate for biomedical applications especially in surgical implant applications.